THE EFFECT OF APPLYING SQ3R METHOD ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Pranata Royganda Sihaloho; Masitowarni Siregar (Universitas Negeri Medan, 2013)
The aim of this study is to discover the effect of applying SQ3R method inreading comprehension. Experimental research design is used as the research method.This research took place at SMA Nasrani 2Medan. There were 2 classes chosen as thesample with 30 students in each class. The classes were divided into two groups namelyexperimental and control group. The experimental group was taught by using SQ3Rmethod and the control group was taught by using conventional method. The instrumentused to collect the data was a set of multiple choice tests, which divided as pre test andpost test. The result of the research was analyzed by using t-test formula. The resultshowed that t-test was higher than t-table (4,23>2,00) at the level of significant 0,05with degree of freedom (df) 58. It means that hypothesis alternative (Ha) is acceptedwhich shows that SQ3R method significantly improves the student’s readingcomprehension.